Pengaruh Latihan Zig Zag Run Untuk Meningkatkan Kelincahan Pada Pemain Sepak Bola Usia 13-15 Tahun Di SMP Muhammadiyah 5 Surakarta - Kinanti, Nurul Fajar, Arif Pristianto, SSt.FT.,M.Fis (2016)
Latar Belakang : Agility is one component of the freshness of the motor is required for all activities that require the speed of change in body position and its parts. To form the agility of a football player aged 13-15 years should be given an exercise that can help improve the agility of the child Tujuan Penelitian : To determine the effect of of zig zag run exercise against football players aged 13-15 years Metode Penelitian : This research is a quasi experimental with pre and post test with control group design, the sample in the treatment group was given exercises zig zag run to run in a zig zag back and forth for 6 times for 4 weeks with a frequency of 3 times a week. Measurements carried out with agility agility t test data were analyzed using the Wilcoxon test to test the effect and influence of different test using Mann Whitney test Hasil Penelitian : Provision of exercise on agility zig zag run soccer players aged 13-15 years after the performed statistical tests obtained using Wilcoxon test pvalue of 0.001 in the treatment group and the control and there is no difference effect after using the Mann Whitney statistical test on get the p-value 0.191 Kesimpulan : There is has effect of exercise on the zig zag run soccer players aged 13-15 years.